INDUSTRI RUMAH TANGGA PANGAN OLAHAN BERBAHAN BAKU IKAN AIR TAWAR PADA KELOMPOK WANITA TANI DI DESA SENDEN, KECAMATAN MUNGKID, KABUPATEN MAGELANG - ernoiz Antriyandarti; susi wuri ani (Trunojoyo University of Madura, 2017)
He majority of the residents of Senden Village, Mungkid Subdistrict, Magelang Regency are farmers with the main commodities of paddy whose income from rice farming is very small due to the narrowness of cultivated land (0.3278 ha). To increase household income, residents maintain freshwater fish in the yard of the house or on farms that pass through irrigation channels. This freshwater fish breed has also not yielded encouraging results due to technical marketing constraints. The contribution of freshwater fish cultivation to farm household income is still small, so a member of Senden Women Farmer Group tries to increase the added value of freshwater fish production by processing it into fish chips. This home-based business is not yet developed and economically feasible yet. Therefore, action research activities are conducted to facilitate the mothers of KWT members to pioneer various processed food business with the abundant raw materials available in the village. This research aims to create productive economic activity of Senden Women Farmer Group in order to increase household income by: (1) giving fish fish cracker, fish nugget and fish meatball training professionally, having commercial value and selling merchandise; (2) facilitating the packaging of processed fish products; (3) to provide technical training and storage management of processed fish products to be durable and maintained its quality.